2017
DOI: 10.1287/isre.2017.0706
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consumers’ Attitudes Toward Controversial Information Technologies: A Contextualization Approach

Abstract: Controversial information technologies, such as biometrics and radio frequency identification, are perceived as having the potential to both benefit and undermine the well-being of the user. Given the type and/or amount of information these technologies have the capability to capture, there have been some concerns among users and potential users. However, prominent technology adoption models tend to focus on only the positive utilities associated with technology use. This research leverages net valence theorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 69 publications
4
49
0
Order By: Relevance
“…This is in line with prior studies (Breward et al, 2017;Warkentin, Goel, & Menard, 2017) that showed that there is a predisposition to view emerging and/or controversial solutions with greater scepticism and worry as when risks and returns are more predictable to users. As we mentioned above, there is a considerable emphasis on constraints across all mental models.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is in line with prior studies (Breward et al, 2017;Warkentin, Goel, & Menard, 2017) that showed that there is a predisposition to view emerging and/or controversial solutions with greater scepticism and worry as when risks and returns are more predictable to users. As we mentioned above, there is a considerable emphasis on constraints across all mental models.…”
Section: Discussionsupporting
confidence: 90%
“…The limiting factors shaped the worldviews of our respondents much more than the action potentials. This is in line with prior studies (Breward et al, 2017;Warkentin, Goel, & Menard, 2017) that showed that there is a predisposition to view emerging and/or controversial solutions with greater scepticism and worry as when risks and returns are more predictable to users. All mental models we discovered exhibit a certain level of controversy and hesitant attitude towards physiolytics, since multiple constraints become salient in the people's appraisals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such contextualization refers to identifying characteristics of the particular context under investigation and incorporating them in the research design (Davison & Martinsons, ; Breward, Hassanein, & Head, 2017). As contextualised studies take the specifics of IS use into account, they can promote the accuracy and relevance of the research findings (Breward, Hassanein, & Head, ), benefit practice by providing empirical insights (Burton‐Jones & Volkoff, ), extend extant theoretical knowledge (Davison & Martinsons, ), and be helpful in better aligning IS use theorizations with how IS are actually employed in real‐life circumstances (Ortiz de Guinea & Webster, ). If the context is left unexamined, the findings can accordingly be inadequate (Breward et al, ; Whetten, ).…”
Section: Introductionmentioning
confidence: 99%
“…As contextualised studies take the specifics of IS use into account, they can promote the accuracy and relevance of the research findings (Breward, Hassanein, & Head, ), benefit practice by providing empirical insights (Burton‐Jones & Volkoff, ), extend extant theoretical knowledge (Davison & Martinsons, ), and be helpful in better aligning IS use theorizations with how IS are actually employed in real‐life circumstances (Ortiz de Guinea & Webster, ). If the context is left unexamined, the findings can accordingly be inadequate (Breward et al, ; Whetten, ). As a result, IS researchers have called for “theories that focus on a specific context” because they “are considered to be vital in providing a rich understanding of a focal phenomenon and to meaningfully extend theories” (Venkatesh, Thong, & Xu, , p. 158).…”
Section: Introductionmentioning
confidence: 99%